Історія Глухівщини 1729–1829 рр. на сторінках домашнього архіву М.О. Марченка - Іванченко, Л.А.; Марченко, М.О. (Сіверщина в історії України, 2018)
У статті зроблено аналіз одного з документів архіву глухівчанина М.О. Марченка. Унікальним є сам
факт збереження рукописів ХVІІІ–ХІХ ст. Мова йде
про копію «Випису» з дворянського зібрання про приналежність роду Саковичів-Даровських до дворянства.
«Випис» містить 20 документів за 100 років, починаючи з кінця ХVІІІ ст., в яких згадуються понад 90 осіб,
містяться дані про посади, які вони обіймали в певні роки, обставини, за яких ці документи було складено. Інформація може бути корисною у краєзнавчих та наукових дослідженнях. В статье сделан анализ одного из документов домашнего архива глуховчанина Н.А. Марченко. Уникальным
является уже сам факт сохранения рукописей XVIII–
ХІХ вв. Речь идёт о копии «Выписке» из дворянского собрания о принадлежности рода Саковичей-Даровских
к дворянству. «Выписка» содержит 20 документов за
100 лет, начиная с конца XVIII ст., в которых упоминаются более 90 лиц, содержатся данные о должностях,
которые они занимали в определённое время, обстоятельства, при которых эти документы были составлены. Информация может быть полезной в краеведческих и научных исследованиях. The article deals with the analysis of one of the documents
of the archivist dweller of Hluhiv region’s M.O. Marchenko.
The very fact of preserving the manuscripts of the 18th-
19th centuries, despite the danger of their being found in
the family of this ethnographer during the Soviet times, is
unique. This is a copy of the «Statement» from the noble
assembly on the affiliation of the genus Sakovychi-Darovski
to the nobility. The «Statement» contains 20 documents for
100 years since the end of the eighteenth century, in which
more than 90 people are mentioned, contains information
about the positions that they occupied in certain years, the
circumstances under which these documents were drawn
up. Information can be useful in local studies and research.